Letrozole-induced endometrial preparation improved the pregnancy outcomes after frozen blastocyst transfer compared to the natural cycle: a retrospective cohort study - Kenji Ezoe; Junichiro Fukuda; Kazumi Takeshima; Kazunori Shinohara; Keiichi Kato (BMC, 2022)
Abstract Background Letrozole treatment is considered an effective option in endometrial preparation for frozen embryo transfers in patients with ovulation disorders or irregular menstruation; however, the effectiveness of letrozole-induced endometrial preparation remains unclear in ovulatory patients. Furthermore, there is no comparative study reporting on pregnancy complications and congenital anomalies after frozen embryo transfers comparing natural and letrozole-assisted cycles. This study examined whether letrozole-induced endometrial preparation affected pregnancy outcomes, perinatal outcomes, and congenital anomalies after single vitrified-warmed blastocyst transfers (SVBTs) in ovulatory patients, as compared with the natural cycle. Methods This historic cohort study included only patients with unexplained infertility. Overall, 14,611 patients who underwent SVBTs between July 2015 and June 2020, comprising both natural and letrozole-assisted cycles, were included. Multiple covariates that impact outcomes were used for propensity score matching; 1,911 patients in the letrozole group were matched to 12,700 patients in the natural group, and the clinical records of 1,910 patients in each group were retrospectively analysed. Cycle characteristics, pregnancy outcomes (clinical pregnancy, ongoing pregnancy, and live birth), and incidence of pregnancy complications and congenital anomalies were statistically compared between the two groups. Results Multivariate logistic regression analysis showed that letrozole administration during SVBT cycles significantly improved the live birth rate (P = 0.0355). Gestational age, birth length, birth weight, and infant sex, as well as the incidence of pregnancy complications and birth defects, were statistically comparable between the two groups. Furthermore, multivariate logistic regression analysis revealed that the perinatal outcomes were not affected by letrozole-induced endometrial preparation. Conclusions Letrozole-induced endometrial preparation improved the live birth rate compared with the natural cycle, without adverse effects on perinatal outcomes and congenital anomalies after SVBTs. Therefore, letrozole-induced endometrial preparation might be a safe and more effective strategy, especially for patients with insufficient luteal function.